MODE, VETEMENTS, TECHNOLOGIE. ESSAI SUR LA PORTABILITE DE LA TECHNIQUE - HEINZEL, Tincuta (Studia Universitatis Babeș-Bolyai Philosophia, 2017)
The present paper addresses the concepts of cloth, fashion and wearable technologies and analysis the way in which cloths and fashion are theorized and the way in which the integration of electronic components and digital devices into the structure of the fabrics are creating precedencies for the transformation of cloth into a technology. By mapping some of the key concepts in fashion theory and their relationship to the definition of personhood, community and society, we are going to show how the first wearable technologies have taken into consideration these concepts in their design processes. Based on our analysis we will emphasize the importance of political stance when it comes to the design of communicative cloths and fashionable technologies.